2001
DOI: 10.1038/84675
|View full text |Cite
|
Sign up to set email alerts
|

Src deficiency or blockade of Src activity in mice provides cerebral protection following stroke

Abstract: Vascular endothelial growth factor (VEGF), an angiogenic factor produced in response to ischemic injury, promotes vascular permeability (VP). Evidence is provided that Src kinase regulates VEGF-mediated VP in the brain following stroke and that suppression of Src activity decreases VP thereby minimizing brain injury. Mice lacking pp60c-src are resistant to VEGF-induced VP and show decreased infarct volumes after stroke whereas mice deficient in pp59c-fyn, another Src family member, have normal VEGF-mediated VP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
284
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(303 citation statements)
references
References 29 publications
15
284
0
1
Order By: Relevance
“…However, in contrast to the role of VEGF in both angiogenesis and VP, we have focused on the role of VP, specifically using a Src-knockout model to characterize mechanisms of tumor-induced VP in tumor growth and invasion. While we cannot exclude the possibility that other tumor-expressed factors may induce VP, we have shown that although VEGF-induced VP is blocked in Srcdeficient mice, VEGF expression in the brain or fibrinogen expression in the plasma is unchanged in src +/− vs. src −/− mice ( [40,60] and data not shown). We propose that the reduction of tumor-induced VP in the brain vascular bed of src −/− mice mediates a reduction in brain tumor infiltration indirectly by regulating the remodeling of the perivascular ECM.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, in contrast to the role of VEGF in both angiogenesis and VP, we have focused on the role of VP, specifically using a Src-knockout model to characterize mechanisms of tumor-induced VP in tumor growth and invasion. While we cannot exclude the possibility that other tumor-expressed factors may induce VP, we have shown that although VEGF-induced VP is blocked in Srcdeficient mice, VEGF expression in the brain or fibrinogen expression in the plasma is unchanged in src +/− vs. src −/− mice ( [40,60] and data not shown). We propose that the reduction of tumor-induced VP in the brain vascular bed of src −/− mice mediates a reduction in brain tumor infiltration indirectly by regulating the remodeling of the perivascular ECM.…”
Section: Discussionmentioning
confidence: 84%
“…Gliomas express a range of growth factors and cytokines, however VEGF is unique among these growth factors in that it induces VP as well as neovascularization [55][56][57][58]. Intra-cranial administration of recombinant VEGF to mice has been shown to increase VP and result in breakdown of the BBB, however the mechanisms regulating this process remain poorly understood [59][60][61]. Therefore, in this study we have examined Src-deficient mice, which we have previously shown to have a 'leakage-resistant' phenotype in response to VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…32 Previous studies revealed that inhibition of the Src family kinases Src or Yes through genetic ablation or a pharmacological inhibitor blocked the VP in response to VEGF and protected mice from tissue damage after myocardial infarction or stroke. [12][13][14] To shed light on the mechanism by which Sema3A induces VP, mice were systemically treated with a Src inhibitor SKI-606 and then challenged with subcutaneous injection of Sema3A or VEGF. While pretreatment with SKI-606 abrogated VEGF-induced VP, it had a minimal effect on Sema3A-induced VP ( Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, we previously showed that genetic or pharmacological inhibition of Src and Yes suppressed VEGF-induced VP, thereby protecting animals from ischemic injury following myocardial infarction and stroke. 12,13 Therefore, the finding that Sema3A suppressed VEGF-mediated VP prompted us to investigate its role as a regulator of VP.…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons montré que rendre inactif Src avant une ischémie transitoire empêche à la fois la potentialisation des récepteurs NMDA et la mort neuronale à long terme des neurones CA1 dans l'hippocampe [15]. Enfin, les inhibiteurs de SKF suppriment l'excitotoxicité dépendante de la suractivation des NMDAR in vitro [15,31] mais diminuent également la surface de lésion cérébrale post-ischémique in vivo [32,33]. Ces résultats suggèrent une implication forte des modulations SKF-NMDAR dans le mécanisme physiopathologique de la mort neuronale induite par l'ischémie [29].…”
Section: Plasticité à Long Terme Des Récepteurs Nmdaunclassified